Eroticism in and of the City: The Question of Approach - Kębłowska-Ławniczak, Ewa (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Discussions of eroticism usually commence with references to Georges Bataille and his L’Erotisme, whose first English edition was published under the title Death and Sensuality: A Study of Eroticism and the Taboo (1962), thus encouraging analyses in terms of transgression. This article opens with a quotation from Zygmunt Bauman’s essay, “On Postmodern Uses of Sex,” which reflects on the instability of the concept and emphasizes its contextualization. This openly declared incongruity raises questions of applicability. What is meant by eroticism today, i.e. in and after postmodernism? The article seeks to explore the relevance of the term in studies of urban drama and tries to suggest a workable approach that would differentiate between the commonly observable erotic material found on display within the premises of the city and the eroticism of the city itself. In the latter case the erotic relationship involves the materiality of the urban context and its user. The essay, focusing on drama, assumes that plays are written for the stage-their proper mode of existence-and deems it necessary to include the city/theatre and city/drama interdependence as well as the nexus of concepts such as urban drama and its genre restrictions into the following analysis.